2018
DOI: 10.1002/ece3.3989
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of rice progenitors in Australia

Abstract: In the thousands of years of rice domestication in Asia, many useful genes have been lost from the gene pool. Wild rice is a key source of diversity for domesticated rice. Genome sequencing has suggested that the wild rice populations in northern Australia may include novel taxa, within the AA genome group of close (interfertile) wild relatives of domesticated rice that have evolved independently due to geographic separation and been isolated from the loss of diversity associated with gene flow from the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 19 publications
(51 reference statements)
3
37
0
Order By: Relevance
“…These variants seem to reflect the heterozygous nature of these plants ( Figure 13). This suggests that they have resulted from hybridisation between these populations in agreement with our overall analysis of the nuclear genes (Moner et al, 2018). Figure 45 -57).…”
Section: Protein Alignment and 3d Structuresupporting
confidence: 85%
See 2 more Smart Citations
“…These variants seem to reflect the heterozygous nature of these plants ( Figure 13). This suggests that they have resulted from hybridisation between these populations in agreement with our overall analysis of the nuclear genes (Moner et al, 2018). Figure 45 -57).…”
Section: Protein Alignment and 3d Structuresupporting
confidence: 85%
“…Intermediate location of those accessions (WR-65 and WR-44) and jumping between clades across all starch related genes was interesting ( Figure 12, 13 and Figure 45-57). Read alignment showed two types of reads that are unlikely to be an error and gave strong evidence of hybridisation between Australian wild rice populations taxa A and B (Moner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the cp genome of Australian O. rufipogon, Jpn1 (taxon A) has a closer relationship to O. meridionalis than to Asian O. rufipogon, although its nuclear type tended to show higher similarity to Asian O. rufipogon. Another perennial species, Jpn2 (taxon B), also shared similarity not only with the cp genome to O. meridionalis but also the nuclear type [14,17,18]. This analysis showed that all Australian wild rice shared some cp genetic similarity with O. meridionalis.…”
Section: Introductionmentioning
confidence: 78%
“…The wild species of genus Oryza is regarded as valuable resource for rice improvement because of its high genetic diversity (Brar, ; Sun, Wang, Li, Yoshimura, & Iwata, ). Application of wild rice to breeding programs can facilitate adaptation to climate change and meet the demand for food security in the face of rapid world population growth (Henry, ; Henry et al, ; Mickelbart, Hasegawa, & Bailey‐Serres, ; Moner et al, ).In this context, Oryza rufipogon and its relatives can provide a rich repository of genes and alleles for potential utilization in rice improvement with the help of genomics‐assisted breeding. Such studies can provide specific insight into natural genetic resources that can be preserved and utilized efficiently.…”
Section: Introductionmentioning
confidence: 99%